Fabrication of Zeolitic imidazolate framework-8 (ZIF-8) modified screen-printed electrode and its catalytic role for the electrochemical determination of biological molecule (dopamine) - Ahmad, Khursheed; Nde, Dieudonne Tanue; Khan, Rais Ahmad; Raza, Waseem (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2024)
Herein, we reported the simple room temperature synthesis of zeolitic imidazolate framework-8 (ZIF-8). The crystallinity and phase of the synthesized ZIF-8 was confirmed by employing powder X-ray Diffraction (PXRD) method. Field emission scanning electron microscopy (FE-SEM) results showed that synthesized ZIF-8 has rhombic dodecahedral structure. The energy-dispersive X-ray spectroscopic (EDX) and photoelectron X-ray spectroscopic (XPS) analysis showed the presence of good phase purity of the synthesized ZIF-8. The screen printed carbon electrode (SPE) has been modified using ZIF-8 as catalyst for the detection of dopamine (DA). The ZIF-8@SPE demonstrated good electrochemical performance for the sensing of DA using cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The ZIF-8@SPE exhibits decent limit of detection (LOD), linear range, and sensitivity of 0.087 µM, 2–50 µM, and 4.78 µA/µM.cm2, respectively. The ZIF-8@SPE also demonstrated good reproducibility, repeatability of 50 cycles and storage stability of 30 days with insignificant change in the performance. The ZIF-8@SPE exhibited decent selectivity for the sensing of DA in presence of various interfering molecules/compounds. We believe that the present work would be beneficial for the scientific scholars working on the development of DA sensors for practical applications.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Dopamine; Electrochemical Sensor; Zeolitic imidazolate framework; ZIF-8